Corporate Social Responsibility, Profitabilitas, Capital Intensity dan Penghindaran Pajak - Maharani, Putu Shandya; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
This study aims to obtain empirical evidence regarding the effect of corporate social responsibility, profitability, and capital intensity on tax avoidance of mining companies listed on Indonesia Stock Exchange in 2013-2017. The method of determining the sample is using purposive sample. The samples were taken from 9 companies with 35 observations. The samples were determining by purposive sampling method. Analysis technique was using multiple regression. Based on the result of research, CSR and profitability have negative effect on tax avoidance. This means the higher CSR and profitability, the lower level of tax avoidance. Meanwhile, capital intensity has positive effect on tax avoidance. This means the higher capital intensity, the higher level of tax avoidance. Keywords: Tax Avoidance; Corporate Social Responsibility; Profitability; Capital Inensity.